A case report of leukoencephalopathy with vanishing white matter disease - Navya, Bommidi; Kondle, Vamshi Krishna; Uppal, Komal (International Journal of Contemporary Pediatrics, 2020)
Vanishing white matter disease (VWM) is one of the most prevalent inherited childhood leucoencephalopathies. Childhood ataxia and diffuse central nervous system hypomyelination are the common findings. The disease is characterized by chronic progressive and episodic deterioration with ataxia, spasticity and optic atrophy. VWM is caused by mutation in any of the five genes encoding the subunits of eukaryotic translation initiation factor eIF2B. The disease has an autosomal recessive mode of inheritance. The cause of the disease is unknown. Authors are reporting an 8 year old male child presented with complaint of difficulty while walking since one month and history viral fever was present one month back. MRI revealed bilateral symmetrical periventricular T2 hyperintensities with T1 hypointensities. Perivenular sparing was seen and molecular analysis shown eIF2B4 mutations confirmation of vanishing white matter disease. No specific treatment is available and advised to avoid stress and triggers.